XDR-TB in South Africa: No Time for Denial or Complacency - Singh, Jerome Amir; Upshur, Ross; Padayatchi, Nesri (PLoS medicine, 2007)
Singh and colleagues discuss the threat to regional and global public health posed by XDR-TB in KwaZulu-Natal, and propose new measures to control the outbreak.